How and why do root apices sense light under the soil surface? - Mo, Mei; Yokawa, Ken; Wan, Yinglang; Baluška, František (Frontiers in Plant Science, 2015)
Light can penetrate several centimetres below the soil surface. Growth, development and behaviour of plant roots are markedly affected by light despite their underground lifestyle. Early studies provided contrasting information on the spatial and temporal distribution of light-sensing cells in the apical region of root apex and discussed the physiological roles of plant hormones in root responses to light. Recent biological and microscopic advances have improved our understanding of the processes involved in the sensing and transduction of light signals, resulting in subsequent physiological and behavioural responses in growing root apices. Here, we review current knowledge of cellular distributions of photoreceptors and their signal transduction pathways in diverse root tissues and root apex zones. We are discussing also the roles of auxin transporters in roots exposed to light, as well as interactions of light signal perceptions with sensing of other environmental factors relevant to plant roots.